Pengaruh Media Sosial Terhadap Partisipasi Pemilih Pemula Pada Pemilihan Presiden dan Wakil Presiden Tahun 2024 - Toni Anwar Mahmud; Eka Tri Puspita Sari; E. Nita Prianti (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
In presidential elections or head of state elections, of course, the people have the right to participate in politics both in voting and being elected. General elections or elections are still considered the most tangible form of public participation in the administration of government. One of them is participation through social media which is often used by teenagers who are also known as beginner voters. With the development of the age, social media has become a part of daily life, especially for the younger generation. This study aims to find out whether there is an influence of social media on the participation of novice voters in the presidential election, to find out how much influence social media has on the participation of the presidential election, and to find out what factors can affect the participation of novice voters in the presidential and vice presidential elections. This research method uses a quantitative method by conducting a survey by distributing a questionnaire in the form of a google form to social media users who follow the social media accounts of the Tangerang Regency General Election Commission (KPU). The sample used consisted of novice voters aged 17-21 years who actively used social media and followed the social media accounts of the General Election Commission (KPU) of Tangerang Regency. Based on the hypothesis test using the F test, Fcal = (0.515) > F table (4.56) is obtained, because Fcal > Ftable, H₀ is rejected and Ha is rejected with a significance of 0.000 < 0.05. So it can be interpreted that simultaneously (Together) there is a positive and insignificant influence between the variables of Social Media and Beginner Voters on the Presidential and Vice Presidential Elections.